A New Wave of Urban Sprawl: Influence of Autonomous Vehicles on the Policy Toolkit and Property Tax Revenue of Local Governments. Issue 3 (2nd October 2021) - Gutierrez, Carlos Ignacio
ABSTRACT: Relatively inexpensive vehicles and public policies that favored a vehicle-centric infrastructure facilitated the movement of families from the confines of urban centers to the periphery of cities in the twentieth century. This phenomenon became known as the first wave of urban sprawl. Its negative effects inspired local policymakers to develop a playbook to fight it, including measures such as zoning and pricing mechanisms directed at commuters, developers, and real estate owners. The advent of autonomous vehicles (AVs) in the twenty-first century promises to benefit society in many ways, including reducing congestion and improving access to transportation. Alternatively, this technology may also instigate a new sprawl that jeopardizes the most important source of local government revenue, property taxes. Using scenario development, this article explores the consequences of a future where residents are willing to trade their AV-generated time savings for homes outside of their local government's jurisdiction, depriving these entities of valuable property tax revenue. It examines how the US policy playbook developed to curtail the first generation of urban sprawl fares in limiting the revenue repercussions of a theoretic AV-induced sprawl.